Influence of Coloured Shade Nets On Growth And Biochemical Constituents In Four Species of Ocimum (Bangladesh Journal of Botany, 2022)
Effects of different coloured shade nets (red, green, black, green, white net) and control (without net) on the biochemical and growth responses in four Ocimum spp. namely O. tenuiflorum L., O. sanctum L., O. basilicum L. and O. gratissimum L. were investigated. Results showed that plants kept under red net consistently outperformed other treatments recording significantly higher growth and biochemical characteristics for all selected Ocimum spp. after 120 days of transplantation. Parameters like shoot length (128.77 ± 4.00 cm), root length (81.48 ± 0.75 cm), leaf number (319.10 ± 3.38), total fresh biomass (158.17 ± 12.82 g/plant) and total dry biomass (63.88 ± 1.37 g/plant) witnessed a 3.38, 2.95, 2.76, 4.17 and 5.16% increase, respectively under red net over control. Plants under red net also recorded a significant increase of 9.68, 14.10 and 28.18% for total phenols (127.50 ± 2.95 mg/g DW), flavonoids (18.33 ± 2.71 mg/g DW) and alkaloids (32.31 ± 2.87 mg/g DW), respectively.Bangladesh J. Bot. 51(3): 547-554, 2022 (September)